CONTROLLING IN THE SYSTEM OF MODERN ENTERPRISE MANAGEMENT - Bezuhlyi, D. V.; Tiutiunnyk, T. V. (Science and Transport Progress, 2006)
The article examines the questions of the needs for improving the management system at a modern enterprise by introduction of controlling. In constantly changing economic conditions, the problem of the enterprise survival and prevention of its bankruptcy comes to be of primary importance. The controlling is an effective instrument of management, whereby it is possible to avoid negative and undesirable results